2018
DOI: 10.3389/fimmu.2018.01503
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Expression of Serum Amyloid A 3 Protects Colon Epithelium Against Acute Injury Through TLR2-Dependent Induction of Neutrophil IL-22 Expression in a Mouse Model of Colitis

Abstract: Induced expression of serum amyloid A (SAA) is a hallmark of many inflammatory diseases, but whether SAA exacerbates inflammation or protects tissues against injury remains unclear. In dextran sulfate sodium (DSS)-induced colitis, SAA3 is the predominant isoform of inducible SAA proteins that also include SAA1 and SAA2, and mice with genetic deletion of Saa3 exhibits increased production of proinflammatory cytokines, decreased expression of IL-22 along with aggravated epithelium disruption, and reduced colon l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 27 publications
1
44
0
Order By: Relevance
“…Five peptides covering the entire lengths of mature SAA1 protein were prepared ( Fig 6A). In vitro characterization of these peptides in SAA1-LPSbinding assays identified Pep 2 (a.a. [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] as being most potent in disrupting the interaction between SAA1 and LPS, in binding assays with a fixed concentration of the peptides and variable concentrations of LPS ( Fig 6B) or a fixed concentration of LPS and variable concentrations of the peptides (Fig 6C). To examine its in vivo effect, Pep 2 or a control peptide with scrambled sequence was injected i.v.…”
Section: Saa1 Binds Lps and Reduces Serum Endotoxin Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Five peptides covering the entire lengths of mature SAA1 protein were prepared ( Fig 6A). In vitro characterization of these peptides in SAA1-LPSbinding assays identified Pep 2 (a.a. [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] as being most potent in disrupting the interaction between SAA1 and LPS, in binding assays with a fixed concentration of the peptides and variable concentrations of LPS ( Fig 6B) or a fixed concentration of LPS and variable concentrations of the peptides (Fig 6C). To examine its in vivo effect, Pep 2 or a control peptide with scrambled sequence was injected i.v.…”
Section: Saa1 Binds Lps and Reduces Serum Endotoxin Levelmentioning
confidence: 99%
“…A recent study reports that, under low pH conditions (pH 3.5-4.5), SAA1 forms soluble oligomers that undergo an ahelix to b-sheet conversion catalyzed by lipid vesicles [27]. Pep 2 (a.a. [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] that disrupts SAA1-LPS interaction overlaps with the second helix of mature SAA1, suggesting that helix II or a 3D structure containing helix II is involved in LPS binding. In addition, the sequence of Pep 2 partially overlaps with SAA fragments (e.g., a.a. 11-58) that were found recently to suppress LPSinduced inflammatory response [33].…”
mentioning
confidence: 99%
“…In addition to mechanosensing, a recent study demonstrated that several metabolites from a consortium of commensal spore‐forming bacteria (predominantly Clostridial species) promote 5‐HT biosynthesis by colonic enterochromaffin cells in colonized mice . In response to microbes, IECs also secrete a number of cytokines and effector molecules including interleukin‐25 (IL‐25) and SAA . These effectors regulate the development and function of intestinal immune cells, as described in the next section of this review.…”
Section: Microbiota–iec Crosstalkmentioning
confidence: 99%
“…37 In response to microbes, IECs also secrete a number of cytokines and effector molecules including interleukin-25 (IL-25) and SAA. 38,39 These effectors regulate the development and function of intestinal immune cells, as described in the next section of this review. Collectively, these recent findings indicate that a broad range of IEC functions are affected by sensing of intestinal microbes (Table 1); however, it is worth noting that many of these studies were performed in the context of pathogenic microbial infection.…”
Section: Microbial Regulation Of Iec Growth and Functionmentioning
confidence: 99%
“…TLR4 was found to mediate SAA-induced expression of iNOS and activation of the related signaling pathways [87]. Despite differences in primary and high-level structures between SAA and the microbial ligands for these receptors, the two TLRs mediate SAA functions both in transfected cells expressing the receptors and in vivo [48,71,79,[88][89][90][91][92]. The identification of the two TLRs as SAA receptors illustrates the possible roles for TLRs in detecting host-derived molecules as a mechanism for alerting immune cells upon exposure to environmental stress.…”
Section: Saa Receptorsmentioning
confidence: 99%